Impaired control of the contact system in hereditary angioedema with normal C1‐inhibitor. Issue 6 (6th February 2020) - Bova, Maria; Suffritti, Chiara; Bafunno, Valeria; Loffredo, Stefania; Cordisco, Giorgia; Del Giacco, Stefano; De Pasquale, Tiziana Maria Angela; Firinu, Davide; Margaglione, Maurizio; Montinaro, Vincenzo; Petraroli, Angelica; Radice, Anna; et al.
Abstract: Background: Hereditary angioedema (HAE) comprises HAE with C1‐inhibitor deficiency (C1‐INH‐HAE) and HAE with normal C1‐INH activity (nl‐C1‐INH‐HAE), due to mutations in factor XII (FXII‐HAE), plasminogen (PLG‐HAE), angiopoietin 1 (ANGPT1‐HAE), kininogen 1 genes (KNG1‐HAE), or angioedema of unknown origin (U‐HAE). The Italian network for C1‐INH‐HAE (ITACA) created a registry including different forms of angioedema without wheals. Objective: We analyzed clinical and laboratory features of a cohort of Italian subjects with nl‐C1‐INH‐HAE followed by ITACA to identify specific biomarkers. Methods: A total of 105 nl‐C1‐INH‐HAE patients were studied. Plasma concentrations of cleaved high‐molecular‐weight kininogen (cHK), vascular endothelial growth factors (VEGFs), angiopoietins (Angs), and secreted phospholipase A2 enzymes (sPLA2 ) were evaluated. Results: We identified 43 FXII‐HAE patients, 58 U‐HAE, and 4 ANGPT1‐HAE. We assessed a prevalence of 1:1.4 × 10 6 for FXII‐HAE and 1:1.0 × 10 6 for U‐HAE. cHK levels in U‐HAE patients were similar to controls in plasma collected using protease inhibitors cocktail (PIC), but they significantly increased in the absence of PIC. In FXII‐HAE patients, cHK levels, in the absence of PIC, were significantly higher than in controls. We found a significant increase of VEGF‐A, VEGF‐C, and Ang1 levels in U‐HAE patients compared to controls. In FXII‐HAE, only VEGF‐C levels were increased. Ang2 concentrations and sPLA2 activity were not modified. The levels of these mediators in ANGPT1‐HAE patients were not altered. Conclusions: Our results suggest that pathogenesis of FXII‐, ANGPT1‐, and U‐HAE moves through an unbalanced control of kallikrein activity, with bradykinin as most likely mediator. VEGFs and Ang1 participate in the pathophysiology of U‐HAE increasing the basal vascular permeability. Abstract : cHK levels in nl‐C1‐INH‐HAE patients are higher than controls in absence of protease inhibitors. Pathogenesis of nl‐C1‐INH‐HAE moves through an unbalanced control of kallikrein activity, with bradykinin as most likely mediator. VEGFs and Ang1 seem to participate in the pathophysiology of U‐HAE increasing the basal vascular permeability. Frequency of angioedema location during attacks differ in the FXII‐HAE, ANGPT1‐HAE and U‐HAE cohorts. Abreviations: angiopoietin 1; ANGP1‐HAE, hereditary angioedema due to mutations in angiopoietin 1; cHK, cleaved high molecular weight kininogen; FXII‐HAE, hereditary angioedema due to mutation in factor XII; nl‐C1‐INH‐HAE, hereditary angioedema with normal C1‐INH activity; U‐HAE, hereditary angioedema of unknown origin; VEGFs, vascular endothelial growth factors